The Influence of Financial Technology on Improving Financial Literacy for MSMEs in Cirebon Regency - Kusnendi, Kusnendi; Hadiyati, Siti Nur (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the influence of Financial Technology (Fintech) on the improvement of MSME financial literacy in Cirebon Regency. In the digital era, Fintech makes it easier to access and use financial services, overcoming obstacles that MSMEs often face such as collateral requirements, remote locations, and high administrative costs. A quantitative approach with Theory of Planned Behavior (TPB) is used to measure the intentions and behaviors of MSMEs in adopting Fintech. The results of the study show that Fintech has a positive effect on the financial literacy of MSMEs by providing easier, faster, and more efficient services, as well as education on the use of digital financial services. This increase in financial literacy helps MSMEs in optimizing financial management, accessing capital, and expanding their businesses. Government and related institutions support is needed for regulations and educational programs to encourage Fintech adoption. This research concludes that Fintech has great potential to increase financial literacy and support the development of MSMEs in the digital era.